STUDENT RESILIENCE IN FACING COVID-19 PANDEMIC VIEWED FROM SOCIAL SUPPORT - Nur Asiyah, Siti; Kumalasari, Mei Lina Fitri; Kusumawati, Estri (Humanities & Social Sciences Reviews, 2020)
Purpose: This study aims to determine the correlation between resilience and social support for students of the Faculty of Psychology and Health at the State Islamic University of Sunan Ampel in Surabaya in participating in academic activities during the COVID-19 pandemic. Methodology: This research uses quantitative methods. The data collection has been done using a questionnaire. Main Finding: The results show that social support can increase student resilience in the face of the COVID-19 pandemic. Applications of this study: The participant of the research is a student of UIN Sunan Ampel Surabaya. Novelty/Originality of this study: COVID-19 pandemic is a very new situation. As well as the government regulations in implementing. Learning causes many mental problems. The results of this study indicate that students need social support to survive through this pandemic.